Effect of black tea on the transverse strength of heat-polymerized acrylic resin - Rahmi, Eni; Agus, Zulkarnain; Putri, Riezka Hanafiah (Padjadjaran Journal of Dentistry, 2017)
Introduction: Heat-polymerized acrylic resin is the most basic denture material used. One of the mechanical properties of an acrylic resin is its transverse strength. The transverse strength test provides an overview of the material’s durability in accepting the load at mastication. Consumption of tea, especially black tea in the world placed the second most consumed. The purpose of this study was to determine the effect of black tea on the transverse strength of heat-polymerized acrylic resin. Methods: This research was an experimental laboratory with 24 samples of heat-polymerized acrylic resin plate with the size of 65x10x2.5 mm. The sample was divided into 6 groups, each consisted of 4 samples. The first, second, and the third groups were immersed in aquadest for consecutively 1, 4, and 20 days. The fourth, fifth, and sixth groups were immersed in the black tea for consecutively 1, 4, and 20 days. The transverse strength was tested using the three-point bending method with the Universal Testing Machine. The results of the transverse strength measurement were then analyzed statistically by the One-way ANOVA test and Holm’s sequential Bonferroni posthoc test as an advanced test. Results: The results of the statistical test showed that p<0.05 (p=0.000) which means that the six groups have a significant difference in the average value of the transverse strength. Conclusion: The conclusion of this research was the black tea immersion duration was affecting the transverse strength differences of the heat-polymerized acrylic resin.